A Truxenone‐based Covalent Organic Framework as an All‐Solid‐State Lithium‐Ion Battery Cathode with High Capacity. Issue 46 (7th September 2020) - Yang, Xiye; Hu, Yiming; Dunlap, Nathan; Wang, Xubo; Huang, Shaofeng; Su, Zhiping; Sharma, Sandeep; Jin, Yinghua; Huang, Fei; Wang, Xiaohui; Lee, Se‐hee; Zhang, Wei
Abstract: All‐solid‐state lithium ion batteries (LIBs) are ideal for energy storage given their safety and long‐term stability. However, there is a limited availability of viable electrode active materials. Herein, we report a truxenone‐based covalent organic framework (COF‐TRO) as cathode materials for all‐solid‐state LIBs. The high‐density carbonyl groups combined with the ordered crystalline COF structure greatly facilitate lithium ion storage via reversible redox reactions. As a result, a high specific capacity of 268 mAh g −1, almost 97.5 % of the calculated theoretical capacity was achieved. To the best of our knowledge, this is the highest capacity among all COF‐based cathode materials for all‐solid‐state LIBs reported so far. Moreover, the excellent cycling stability (99.9 % capacity retention after 100 cycles at 0.1 C rate) shown by COF‐TRO suggests such truxenone‐based COFs have great potential in energy storage applications. Abstract : A truxenone‐based covalent organic framework (COF) was applied as the cathode material for an all‐solid‐state Li‐ion battery with a high experimental capacity of 268 mAh g −1 . A 6 Li + insertion mechanism for the truxenone moiety was revealed by the combination of experiment and theory, which paves the way for the development of multiple‐electron redox‐active COF materials.